2014
DOI: 10.1177/1076029614562952
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Programmed Death 1 (PD-1) Is Decreased in Patients With Immune Thrombocytopenia (ITP)

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disease characterized by dysregulation of T cells. Programmed death (PD) 1 and programmed death 1 ligand 1 (PD-L1) are cosignaling molecules, and the major role of the PD-1 pathway is the inhibition of self-reactive T cells and to protect against autoimmune diseases. We measured levels of serum soluble PD 1 (sPD-1) and serum soluble PD-L1 (sPD-L1) in 67 patients with ITP (24 newly diagnosed ITP [ndITP], 43 chronic ITP [cITP]) and 21 healthy controls (HCs). We dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 15 publications
1
18
1
1
Order By: Relevance
“…To further explore the reason for the impaired cell-tocell contact regulation, we also investigated the expressions of PDCD1 and ICOS on the CD8 + CD28 À surface using FACS. Although it was reported that PDCD1 mRNA expression in PBMCs and soluble PDCD1 in serum was decreased in ITP patients (Birtas Atesoglu et al, 2016;Zhong et al, 2016), we did not find any difference in PDCD1 expression on CD8 + CD28 À Ts cells between ITP patients and controls. This result suggested that PDCD1 might not be associated with the Ts defect in ITP patients.…”
Section: Discussioncontrasting
confidence: 95%
“…To further explore the reason for the impaired cell-tocell contact regulation, we also investigated the expressions of PDCD1 and ICOS on the CD8 + CD28 À surface using FACS. Although it was reported that PDCD1 mRNA expression in PBMCs and soluble PDCD1 in serum was decreased in ITP patients (Birtas Atesoglu et al, 2016;Zhong et al, 2016), we did not find any difference in PDCD1 expression on CD8 + CD28 À Ts cells between ITP patients and controls. This result suggested that PDCD1 might not be associated with the Ts defect in ITP patients.…”
Section: Discussioncontrasting
confidence: 95%
“…Plenty of studies have demonstrated that sPD-1 and sPD-L1 were involved in autoimmune disease, such as systemic lupus erythematosus (SLE) [13], autoimmune type 1 diabetes [14], Immune thrombocytopenia (ITP) [15] rheumatoid arthritis (RA) [16] and chronic hepatitis B [17], while few was reported on sJIA. Our previous study have reported decreased PD-1 on CD4 + T cell and reduced PD-L1 on mDC (myeloid dendritic cell) in active sJIA patients [18].…”
Section: Introductionmentioning
confidence: 99%
“…Such blockade leads to restoration of T‐cell activity that can lead to enhancement of anti‐tumor immune responses. Although sPD‐1 is found in healthy individuals, its concentration increases in patients with autoimmune diseases . Interestingly, several studies have shown correlation between the levels of sPD‐1 in patient sera and cancer progression.…”
Section: Immune Checkpoint Molecules: Regulating the Immune Response mentioning
confidence: 99%
“…Although sPD-1 is found in healthy individuals, its concentration increases in patients with autoimmune diseases. [106][107][108] Interestingly, several studies have shown correlation between the levels of sPD-1 in patient sera and cancer progression. sPD-1 levels correlate with sustained high hepatitis B viral load and increased risk of hepatocellular carcinoma.…”
Section: Spd-1 In Cancer Prognosismentioning
confidence: 99%